PERLUNYA REAKTUALISASI PENDIDIKAN AGAMA DI SEKOLAH - MARZUKI, MARZUKI (Universitas Negeri Yogyakarta, 2003)
We deserve to thank God und hmv been proud to the fast growing of religious activities within the social life recently. However, unfortunately, crimes or criminalities are growing fast in the society, from drunkhard, thief, robbery, adultery, deceit, corruption till the raping and killing as well as the conflict among religious followers. If the causal (actor is the religious education it self the religious education needs to be actualized, or in the other word there is necessary any reactualitation of religious education. Those factors, one by one, need to he anticipated. From the educational perspective, effort to be undertaken are the improvement of our religious education quality concerning its material, teaching method teachers, environment, etc. From this point, the other causal factors would be able to be gradually overcome.